Low Doses of Camptothecin Induced Hormetic and Neuroprotective Effects in PC12 Cells - Chao Zhang; Shenghui Chen; Jiaolin Bao; Yulin Zhang; Borong Huang; Xuejing Jia; Meiwan Chen; Jian-Bo Wan; Huanxing Su; Yitao Wang; Chengwei He (SAGE Publishing, 2015)
Hormetic response is an adaptive mechanism for a cell or organism surviving in an unfavorable environment. It has been an intriguing subject of researches covering a broad range of biological and medical disciplines, in which the underlying significance and molecular mechanisms are under intensive investigation. In the present study, we demonstrated that topoisomerase I inhibitor camptothecin (CPT), a potent anticancer agent, induced an obvious hormetic response in rat pheochromocytoma PC12 cells. Camptothecin inhibited PC12 cell growth at relative high doses as generally acknowledged while stimulated the cell growth by as much as 39% at low doses. Moreover, low doses of CPT protected the cells from hydrogen peroxide (H 2 O 2 )-induced cell death. Phosphoinositide 3-kinase (PI3K)/Akt and nuclear factor-E2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) pathways were reported playing pivotal roles in protecting cells from oxidative stress. We observed that these 2 pathways were upregulated by low doses of CPT, as evidenced by increased levels of phosphorylated PI3K, phosphorylated Akt, phosphorylated mammalian target of rapamycin, Nrf2, and HO-1; and abolishment of the growth-promoting and neuroprotective effects of CPT by LY294002, a PI3K inhibitor. These results suggest that the hormetic and neuroprotective effects of CPT at low doses on PC12 cells were attributable, at least partially, to upregulated PI3K/Akt and Nrf2/HO-1 pathways.